Variations, relations and clinical significance of carotid arterial system in anterior neck: a cadaveric study - Ghosh, Anasuya; Chaudhury, Subhramoy; Datta, Atin (International Journal of Research in Medical Sciences, 2019)
Background: The common carotid, internal and external carotid arteries and their branches serve as major source of blood supply in head-neck region of human and are often encountered during numerous surgical and clinical interventions of neck. Methods: We dissected and examined both sides of neck in 49 well embalmed cadavers (98 sides). We recorded the following anatomical parameters of carotid arterial system-level of bifurcation, the relation between internal and external carotid arteries, branching pattern of anterior branches of external carotid artery, tortuosity in carotid arterial system, and relation of hypoglossal nerve with the carotid arteries. Results: In 56.16 % cases, the common carotid arterial bifurcation took place at the upper border of thyroid cartilage though high bifurcation was quite common (43.88%). The external carotid artery was located antero-medial to internal carotid artery in most cases (93.87%). Abnormal tortuosity of carotid arterial system was detected in 2.04% cases only. In 86.73% cases, the hypoglossal nerve crossed the internal and external carotid artery superior to carotid bifurcation above the level of hyoid bone while in 1 case it crossed immediately inferior to carotid bifurcation. In branching pattern, following variations were observed- linguo-facial trunk in 15.3% cases, thyro-lingual trunk in 5.1% cases, origin of superior thyroid artery from common carotid in 10.02% cases and origin of superior thyroid from internal carotid in one case (1.02%). Conclusions: The carotid arterial system has complex and variable anatomy in neck and this information should be kept in mind to avoid unwanted damage during surgical procedures of neck.